User interface design elements for user-friendly reading experience of webcomic on mobile application/ Nurlisa Athirah Baharuddin and Anwar Fikri Abdullah - Baharuddin, Nurlisa Athirah; Abdullah, Anwar Fikri (Universiti Teknologi MARA, Perak, 2024)
The research is to identify the elements of interface design to improve the overall reading experience of webcomic applications. Webcomic, is a form of comic art that is primarily distributed and consumed on the internet. They are essentially comic strips or graphic novels that are published digitally and made accessible to a wide audience through various websites or dedicated platforms. It is of the utmost importance to understand how to create a user-friendly interface design that can cater to both comic creators and readers as webcomics continue to gain popularity in digital readers nowadays. This paper sets out to identify various interface design elements, mobile applications features and strategies that can contribute to a more user-friendly and visually pleasing interface for webcomic applications using applied literary analysis. Therefore, all the data was gathered through studies of past research and the data collected are made into use in designing a user-friendly webcomic application. This paper aimed at emphasizing the importance studies of user-friendly interface design elements in webcomic applications that can serve to promotes artist’s expression, storytelling, and improve community alias digital reader’s interaction.